Aluminum sludge-polyurethane prepolymer adsorption material and preparation method and application thereof
By mixing and foaming anhydrous aluminum sludge powder with water and polyurethane prepolymers, a high-porosity, lightweight and stable aluminum sludge-polyurethane prepolymer adsorption material is prepared, which solves the problem of insufficient pore structure of the aluminum sludge matrix, improves the adsorption performance and structural stability, and achieves the purpose of waste control.
Patent Information
- Application Number
- CN202411865220.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The pore structure of the existing aluminum sludge matrix is not well developed enough, resulting in poor breathability, affecting the growth of microorganisms and the uniformity of water flow in artificial wetlands, and at the same time, it is easy to form plate cleavage, reducing the permeability and adsorption properties of the matrix.
By mixing and foaming anhydrous aluminum sludge powder with water and polyurethane prepolymers, an aluminum sludge-polyurethane prepolymer adsorption material is prepared to form a high porosity, lightweight and stable adsorption material.
The porosity and structural stability of the adsorbed materials are improved, their adsorption performance on pollutants is enhanced, and the breathability and permeability of traditional aluminum sludge substrates is solved, and the purpose of waste control is achieved.
Smart Images

Figure CN119318950B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sludge resource utilization, and more specifically, to an aluminum sludge-polyurethane prepolymer adsorption material and a preparation method and application thereof. Background Art
[0002] The artificial wetland matrix not only provides space for the growth and reproduction of plants and microorganisms, but also plays an important role in artificial wetlands as a place for the adsorption and filtration of water-extracted pollutants. The properties of the matrix in artificial wetlands are directly related to the removal rate of pollutants in sewage, the water extraction flow rate, and the size of the wetland area. Traditional artificial wetland matrices are generally composed of gravel, crushed stone, sand, and broken bricks, and different matrix combinations and proportions are selected according to the water quality. In recent years, porous matrices with large specific surface areas and adsorption properties such as ceramsite, fly ash, and blast furnace slag have been used in artificial wetlands. However, the existing matrix is large in mass, resulting in high transportation and loading costs, and the problem of artificial wetland matrix clogging has always been a bottleneck for artificial wetlands. Therefore, it is urgent to develop a new artificial wetland matrix that is lightweight, porous, and has high phosphorus adsorption performance, which is of great significance for the future development of artificial wetlands.
[0003] In the coagulation and sedimentation processes of water treatment, sludge will inevitably be produced due to the addition of coagulants such as aluminum salts (polyaluminum chloride, polyaluminum sulfate) and iron salts. Aluminum salts are the most widely used coagulants in the world. The sludge produced by using aluminum salts such as aluminum sulfate and polyaluminum chloride as coagulants is aluminum sludge. Aluminum sludge usually appears as gray, grayish white or dark gray muddy substances. The texture is relatively fine and has a certain viscosity. Its particle size range is wide, ranging from a few microns to hundreds of microns. The smaller particle size increases its specific surface area, which has a certain effect on its adsorption performance. Aluminum sludge contains a certain amount of microorganisms, including bacteria, fungi, etc. They play a complex role in the ecological environment of aluminum sludge, such as participating in the decomposition of organic matter. When aluminum sludge is used in applications such as artificial wetland substrates, these microorganisms may also have a certain impact on the ecological processes in the wetland system. Therefore, aluminum sludge is used in the sewage treatment industry to replace traditional substrates such as sand and gravel, and has become a new substrate for artificial wetlands.
[0004] However, the current utilization of aluminum sludge is relatively simple, mainly collecting aluminum sludge from water plants, drying it in a cool environment to reduce its moisture content to about 45%, and then putting the dried aluminum sludge into a briquetting machine for granulation to obtain aluminum sludge particles. The aluminum sludge particles are then screened to remove particles that are too large or too small to obtain aluminum sludge particles of appropriate particle size, and aluminum sludge particles of different particle sizes are assembled into an artificial wetland matrix.
[0005] However, the aluminum sludge that has not undergone foaming treatment has an underdeveloped pore structure and a relatively low porosity, which will result in poor air permeability of the matrix, adversely affecting the growth and metabolism of aerobic microorganisms in artificial wetlands, limiting the speed and uniformity of water flow through the matrix, reducing the hydraulic retention time of the artificial wetland, and resulting in insufficient contact time between the sludge and the matrix. In addition, the aluminum sludge particles have strong adhesion and are prone to compaction during long-term use. Compaction will further reduce the permeability of the matrix and hinder the circulation of water and gas. Over time, pollutants adsorbed in the aluminum sludge matrix gradually accumulate and will be released again.
[0006] Therefore, aluminum sludge needs to be further processed to obtain porous, lightweight adsorption materials with efficient phosphorus absorption effects, which is of great significance for the development of artificial wetland fillers. Summary of the invention
[0007] In order to further process aluminum sludge to obtain an adsorption material that is porous, lightweight and has a high efficiency in phosphorus absorption, the present application provides an aluminum sludge-polyurethane prepolymer adsorption material and a preparation method and application thereof.
[0008] In the first aspect, the present application provides a method for preparing an aluminum sludge-polyurethane prepolymer adsorption material, using the following technical solution:
[0009] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material comprises the following steps:
[0010] S1, mechanically dehydrating and drying the collected aluminum sludge, crushing it, and grinding it to obtain anhydrous aluminum sludge powder;
[0011] S2, mixing anhydrous aluminum sludge powder with water and polyurethane prepolymer, stirring and foaming;
[0012] S3, standing and solidifying, and then air-drying to obtain aluminum sludge-polyurethane prepolymer adsorption material.
[0013] By adopting the above technical scheme, the present application adopts the simplest method to mix aluminum sludge powder, water and polyurethane prepolymer to prepare a new aluminum sludge-polyurethane prepolymer adsorption material, which can be used as an adsorbent in sewage treatment and as a new artificial wetland filler. The prepared adsorption material has the characteristics of high porosity, soft texture and no slag. In particular, for the current method of mixing polyurethane raw materials with hydrous aluminum sludge for foaming, the present application mixes anhydrous aluminum sludge with polyurethane prepolymer and water for foaming, and water is used as a binder and a regulator. The isocyanate group in the polyurethane prepolymer combines with water to produce a foaming chain extension reaction, and the water molecules are between the polyurethane molecules. Hydrogen bonds are formed between the particles to form a foam structure, thus obtaining an adsorbent material with higher porosity and lower density. More importantly, the addition of water can improve the stability of the adsorbent material. The prepared adsorbent material will not fall off, and is more convenient for transportation and construction. In addition, due to the presence of aluminum in the aluminum sludge, it has excellent phosphorus removal performance. In this application, a porous lightweight adsorbent material is formed by compounding aluminum sludge and polyurethane prepolymer with a polyurethane prepolymer as a skeleton, and the polyurethane prepolymer reacts with water to form a foamed porous structure, which not only solves the problem of aluminum sludge being easily lost in water and causing blockage in artificial wetlands, but also solves the problem of the final disposal of aluminum sludge, thereby achieving waste treatment with waste, and also solves the problems of blockage and inconvenience in construction of artificial wetlands.
[0014] In addition, the adsorption material prepared by the prepolymer method of the present application has better structural stability, reduces the risk of slag falling, and the process is simpler and more convenient, suitable for industrial automated production, improves production efficiency, simplifies the production process, and can be foamed by rapid stirring under normal temperature conditions, reducing energy consumption and costs, and is easy to implement on an industrial scale, which is conducive to mass production. It is found that the adsorption material prepared by the method provided in the present application has excellent removal effects on the antibiotics norfloxacin hydrochloride, oxytetracycline hydrochloride, and sulfonamide and quinolone antibiotics, sulfamethoxazole and norfloxacin, which is of great significance for the removal of antibiotic wastewater.
[0015] Optionally, in step S2, water and anhydrous aluminum sludge powder are first stirred to form a uniform slurry mixture, and then the polyurethane prepolymer is added and stirred for foaming at room temperature.
[0016] By adopting the above-mentioned scheme, in the present application, water and anhydrous aluminum sludge powder are first mixed evenly and then the polyurethane prepolymer is added. With the addition of the polyurethane prepolymer, the foaming reaction becomes more intense, and the formed polyurethane soft foam has a higher porosity. The aluminum sludge-polyurethane prepolymer adsorption material finally obtained has a better porosity. The high porosity increases the surface area in contact with pollutants and has a good soft texture. Combined with a uniform mud mixture and a uniform foaming process, it has better structural stability, reduces the risk of slagging, and is more convenient for transportation and application. In addition, the adsorption material does not slag, so that the solid suspended matter content in the water will not be increased during the wastewater treatment process, and the treatment effect will not be affected, and the treatment effect has a more lasting effect.
[0017] Optionally, in step S2, the mass ratio of anhydrous aluminum sludge powder to water is (15-25):10, and the mass ratio of water to polyurethane prepolymer is 10:(3-7).
[0018] By adopting the above technical scheme, in this application, by adjusting the ratio of the above three raw materials, an adsorption material with light weight, richer porosity and good removal performance is finally obtained, which will not float when used in artificial wetlands, and has good structural stability and will not fall off, thereby improving the treatment effect and being more convenient for transportation.
[0019] Optionally, the weight average molecular weight of the polyurethane prepolymer is 1200-1800, more preferably 1500.
[0020] By adopting the above technical scheme, an adsorption material with richer porosity is obtained by controlling the molecular weight of the polyurethane prepolymer. If the molecular weight of the polyurethane prepolymer is too large, the longer the molecular weight, the more difficult it will be to foam, and it will be easy to entangle during the foaming process, which will affect the hard gas stability and foam uniformity. In addition, the polyurethane prepolymer with a moderate molecular weight has a moderate reactivity, can react quickly with water and produce stable foam. The polyurethane prepolymer with a molecular weight in this application is selected, and the addition ratio between the anhydrous aluminum sludge powder and water and the polyurethane prepolymer is adjusted, so that the adsorption material finally has a richer pore structure and a better adsorption and removal effect.
[0021] Optionally, in step S2, the mass ratio of anhydrous aluminum sludge powder to water and polyurethane prepolymer is 20:10:3.
[0022] By adopting the above technical solution and selecting the above added mass ratio, the adsorption material has better comprehensive properties such as high porosity, good removal performance, soft texture and not easy to fall off.
[0023] Optionally, the specific operations in step S1 are: mechanically dehydrating the collected aluminum sludge, drying it in the sun, air-drying it, crushing it, grinding it and sieving it to obtain anhydrous aluminum sludge powder.
[0024] Optionally, the anhydrous aluminum sludge powder in step S1 is sewage aluminum sludge powder obtained after passing through an 80-150 mesh sieve.
[0025] By adopting the above technical solution, when the particle size of the aluminum sludge powder is too large, the aluminum sludge particles of the aluminum sludge matrix and the polyurethane prepolymer cannot be well combined together. This is because the sludge particle size is too large, so after the sludge particles and water are mixed and stirred, the sludge particles will sink quickly and cannot be evenly suspended and distributed in the water. The mixture of sludge powder and water will show obvious stratification. When the aluminum sludge particle size gradually decreases, the density of the adsorption material gradually decreases, and its water absorption and phosphorus absorption capacity gradually increase. However, when the aluminum sludge particle size is too small, its structural integrity is reduced. When the above particle size range is selected, its comprehensive performance is better.
[0026] Optionally, a modified PET-gasified slag composite filler is also added in step S2, and the added amount of the modified PET-gasified slag composite filler is 10-18% of the added amount of anhydrous aluminum sludge powder. The modified PET-gasified slag composite filler is obtained by mixing waste polyester and gasified slag, calcining at 420-500°C for 2-3h, and then treating with N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane.
[0027] By adopting the above technical scheme, the present application also adds a modified PET-gasified slag composite filler, which is formed by recycling two kinds of waste, polyester waste and gasified slag. The gasified slag is a solid waste produced by the reaction of coal and other fuels under high temperature and high pressure conditions in a gasifier, and contains oxides such as ferroferric oxide and silicates. Under the catalytic action of the oxides of the gasified slag itself, the waste polyester can achieve its semi-carbonization process at low temperature to form a composite of polyester carbon skeleton-gasified slag carbon skeleton, and then it is treated with N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane to introduce hydroxyl and The amino functional group is then added together with the aluminum sludge powder. On the one hand, its carbon skeleton can be used to load the aluminum sludge powder, further improving the stability of the final adsorption material. Combined with the polyurethane prepolymer and water foaming, a unique pore structure is formed. The final adsorption material has a certain weight, which will not float in the artificial wetland and will not fall off. In addition, the hydroxyl and amino functional groups introduced on the surface of the gasified slag can form chemical bonds with the antibiotics in the sulfamethoxazole and norfloxacin antibiotic wastewater, which is more conducive to the removal of antibiotics, further improving the removal potential for emerging pollutant antibiotics, and further realizing the reuse of waste polyester and solid waste gasification slag.
[0028] Optionally, the waste polyester and gasified slag are mixed and calcined and then firstly subjected to acid leaching in a sulfuric acid solution, then filtered and separated and then washed with water to obtain a primary filler, which is then treated with N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane.
[0029] By adopting the above technical scheme, the filler obtained by mixing and calcining the waste polyester and gasification slag is first subjected to acid leaching and then water washing, so that the aluminum silicate in the gasification slag can be dissolved to form soluble aluminum salts, and then combined with aluminum sludge to further improve the phosphorus removal effect.
[0030] Optionally, the mass ratio of waste polyester and gasified slag is 1:(1.8-2.2), and the mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane is 1:(2-3), and the amount of 3-hydroxypropyltrimethoxysilane added is 5-10wt% of the amount of gasified slag added.
[0031] Optionally, the modified PET-fumed slag composite filler is prepared by the following method:
[0032] The waste polyester and gasified slag are mixed and calcined at 420-500°C for 2-3h, then immersed in dilute sulfuric acid with a mass concentration of 37-45wt% for 20-40min, filtered and separated, washed with water, and then immersed in a mixed aqueous solution of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane for 1-2h and dried, the immersion temperature is 35-50°C, to obtain a modified PET-gasified slag composite filler.
[0033] Optionally, PAMAM is added together with N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane, and the amount of PAMAM added is 3-5wt% of the amount of gasified slag added.
[0034] By adopting the above technical scheme, the addition of PAMAM can further introduce amide and amino functional groups on the gasification slag, enhance the adsorption performance of sulfamethazine and norfloxacin, and thus improve the removal effect of sulfamethazine and norfloxacin in antibiotic wastewater.
[0035] In the second aspect, the present application provides an aluminum sludge-polyurethane prepolymer adsorption material, which adopts the following technical solution:
[0036] An aluminum sludge-polyurethane prepolymer adsorption material is prepared by the preparation method as described above.
[0037] By adopting the above technical scheme, the adsorption material in the present application uses aluminum sludge, polyurethane prepolymer and water as raw materials. Aluminum sludge has good adsorption performance for some pollutants and will not have any impact on the environment. In addition, the content of pollutants in aluminum sludge is small and will not harm the plants cultivated therein. Aluminum sludge is easy to cause blockage due to its loose texture. Therefore, in the present application, polyurethane prepolymer and aluminum sludge are combined together to improve the flexibility and adhesion of aluminum sludge, and fill the pores to increase the density of aluminum sludge. Combined with the bonding and harmonizing effects of water, the final adsorption material has a suitable density and will not float in the artificial wetland. It is also lighter, easier to transport and use, and will not slag, thereby preventing the change of the solid suspended matter content in the water due to slag dropping, affecting the wastewater treatment effect.
[0038] Finally, the adsorption material provided by this application uses aluminum sludge and polyurethane prepolymer. The slurry formed by stirring aluminum sludge with water is mixed with polyurethane prepolymer for foaming. This can be completed in a short time at room temperature without high temperature and long time, thus reducing energy consumption and greenhouse gas emissions. There is no need to use complex processes such as ball presses and adhesives. With simple operation, a soft and highly absorbent adsorption material can be foamed, which can be used as artificial wetland matrix filler, can be mass-produced and applied on a large scale, is easy to transport, has high phosphorus removal performance, and does not fall off.
[0039] In a third aspect, the present application provides an application of an aluminum sludge-polyurethane prepolymer adsorption material, using the following technical solution:
[0040] As described above, an aluminum sludge-polyurethane prepolymer adsorption material is used in the field of artificial wetland filler or sewage treatment.
[0041] In summary, this application has the following beneficial effects:
[0042] 1. The adsorbent material obtained in the present application has high porosity and good pollutant removal performance. The obtained adsorbent material has better air permeability and water retention capacity. At the same time, the high porosity increases the surface area in contact with the pollutants, thereby improving the removal efficiency. In addition, the aluminum sludge itself has high adsorption performance, and combined with the porous structure of the polyurethane soft foam, the obtained adsorbent material exhibits excellent pollutant removal ability, especially for antibiotic wastewater. It also has excellent removal effect;
[0043] 2. The adsorption material based on aluminum sludge prepared by the prepolymer method in the present application has a good soft texture, and due to its uniform slurry mixture and uniform foaming process, it has good structural stability and is not easy to fall off, so that the solid suspended matter content in the water will not be increased during the treatment of wastewater, and the treatment effect will not be affected;
[0044] 3. The method provided by the present application can foam by rapid stirring at room temperature, and only needs to mix water, polyurethane prepolymer and aluminum sludge. The process is simplified, batch production is possible, and it is suitable for industrial automated production, improving production efficiency, simplifying the production process, reducing energy consumption and cost, and being easy to implement on an industrial scale, which is conducive to batch production;
[0045] 4. In this application, aluminum sludge is used as raw material to achieve waste treatment, which is conducive to waste recycling, reducing environmental pollution and treatment costs. In addition, compared with traditional artificial matrix fillers, the adsorption material obtained by foaming the polyurethane prepolymer and aluminum sludge in this application has the characteristics of light weight, making transportation more convenient, and the high porosity reduces the weight of the material, further reducing the transportation cost, and the obtained material is environmentally friendly;
[0046] 5. In this application, aluminum sludge is used as raw material to reduce the production cost of new materials, and at the same time, a way of waste utilization is provided, which increases the economy and sustainability of the materials and is conducive to large-scale application. Moreover, the preparation process of the adsorption material based on aluminum sludge in this application is environmentally friendly and realizes the reuse of industrial by-products. Large-scale application can reduce the exploitation of natural resources, reduce the environmental footprint, and achieve more green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a product flow chart of the method in Example 1 of the present application;
[0048] Figure 2 is an appearance diagram of the adsorption material prepared in Example 1 of the present application;
[0049] Figure 3 is a cut-away cross-sectional view of the adsorbent material obtained in Example 1 of the present application;
[0050] Figure 4 This is a product diagram of adsorption materials made from aluminum sludge powder with different particle sizes in the embodiments of the present application;
[0051] Figure 5 It is a product diagram of the adsorption material obtained by different water-to-binder ratios (water and polyurethane addition mass ratios) in the embodiments of the present application;
[0052] Figure 6 This is a product diagram of the adsorption material obtained with different solid-liquid ratios (mass ratio of water and anhydrous aluminum sludge powder added) in the embodiments of the present application. DETAILED DESCRIPTION
[0053] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0054] The anhydrous in the anhydrous aluminum sludge powder in this application means that the water content in the aluminum sludge powder is less than or equal to 3wt%.
[0055] The polyurethane prepolymer in the following examples is a polyurethane prepolymer model HF131 purchased from Shenzhen Tanlian Technology Co., Ltd., and its weight average molecular weight is 1500.
[0056] Example 1
[0057] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material comprises the following steps:
[0058] S1. Mechanically dehydrate the collected aluminum sludge, dry it, air-dry it, crush it, and grind it through an 80-mesh sieve to obtain anhydrous aluminum sludge powder with a mesh size less than 80;
[0059] S2. Combination Figure 1 First, water and anhydrous aluminum sludge powder are stirred to form a uniform slurry mixture, and then the polyurethane prepolymer is added, mixed and stirred at room temperature for 30 seconds, and foamed to form blocks, wherein the mass ratio of the anhydrous aluminum sludge powder to water is 15:10, and the mass ratio of water to polyurethane prepolymer is 10:5;
[0060] S3, let it stand for 2-5 minutes to solidify, and then air-dry to obtain aluminum sludge-polyurethane prepolymer adsorption material. Figure 2 and Figure 3 .
[0061] Example 2-3
[0062] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 1, except that in step S1, anhydrous aluminum sludge powder is obtained by sieving with 150 mesh and 220 mesh sieves respectively to obtain an adsorption material such as Figure 4 .
[0063] Example 4
[0064] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 1, except that step S2 is carried out after passing through a 30-mesh sieve in step S1. It can be seen that when the sieve mesh number is too small and the particle size of the anhydrous aluminum sludge powder particles is too large, after mixing and stirring with water, the particles will sink and cannot be evenly suspended and distributed in the water, causing the mixture of sludge and water to be obviously stratified. After the polyurethane prepolymer is subsequently added, the aluminum sludge and the polyurethane prepolymer cannot be well combined together.
[0065] In Examples 1-3, the particle size of the anhydrous aluminum sludge particles gradually decreases, and the stratification phenomenon of the aluminum sludge particles mixed with water is significantly improved, so that a uniform and stable slurry can be formed.
[0066] The density, water absorption and phosphorus absorption performance of the adsorbent materials obtained in the above Examples 1-3 are shown in Table 1 below.
[0067] Table 1:
[0068]
[0069] It can be seen that as the sludge particle size gradually decreases, the density of the adsorption material gradually decreases, while the water absorption and phosphorus absorption capacity of the adsorption material gradually increase as the particle size decreases, and the particle size of aluminum sludge powder has the greatest influence on the phosphorus absorption capacity.
[0070] Embodiment 5-7
[0071] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 1, except that: in step S2, the mass ratio of anhydrous aluminum sludge powder to water is 20:10, and the mass ratio of water to polyurethane prepolymer is 10:3, 10:5, and 10:7, respectively, to obtain an adsorption material such as Figure 5 As shown, it can be seen that when the amount of polyurethane prepolymer added is small, that is, the mass ratio of water to polyurethane prepolymer is 10:3, the foaming of the adsorption material is not obvious and the volume is small, and the gaps between the sludge particles are relatively dense. The amount of polyurethane prepolymer added gradually increases. When the mass ratio of water to polyurethane prepolymer is 10:7, it is obviously observed that larger pores appear in the adsorption material.
[0072] In addition, the density, water absorption, and phosphorus absorption capacity of the adsorption materials obtained with different water-to-binder ratios (mass ratio of water to polyurethane prepolymer added) in the above Examples 5-7 were measured, and the results are shown in Table 2 below.
[0073] Table 2:
[0074]
[0075] Referring to Table 2 above, it can be seen that the added mass ratio of water to polyurethane prepolymer has a significant effect on the water absorption of the adsorbent material, but has little effect on the phosphorus absorption capacity.
[0076] Embodiment 8-9
[0077] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 1, except that the mass ratio of water to polyurethane prepolymer added in step S2 is 10:3, and the mass ratio of anhydrous aluminum sludge powder to water added is 25:10 and 15:10, respectively. The obtained adsorption material is as follows Figure 6 shown.
[0078] The density, water absorption and phosphorus absorption capacity of the adsorbent material prepared in the above examples are tested and the results are shown in Table 3 below.
[0079] Table 3:
[0080]
[0081] Combining the test results of Example 5 in Table 3 and Table 2 above, it can be seen that when the mass ratio of anhydrous aluminum sludge powder to water is 20:10 and the mass ratio of water to polyurethane prepolymer is 10:3, the density of the adsorbent material is 0.20 g / cm 3 It will not float when used as a matrix for artificial wetlands. It also has good water and phosphorus absorption capabilities. Its comprehensive performance makes it more suitable as a matrix for artificial wetlands.
[0082] In addition, it can be seen that the adsorption materials prepared in Examples 1-9 of the present application do not fall off, so that the solid suspended matter content in the water will not be increased during the wastewater treatment process, and the treatment effect will not be affected.
[0083] In addition, the adsorption material obtained by adding anhydrous aluminum sludge powder to water in Example 5 of the present application in a mass ratio of 20:10 and a mass ratio of water to polyurethane prepolymer of 10:5 was used as the experimental material, and the adsorption kinetics of phosphorus were studied. It was found that 10 mg / L of phosphorus-containing wastewater was used as the experimental wastewater, and 1g of the adsorption material was subjected to an adsorption experiment. The results showed that the removal rate of phosphorus reached more than 98%. In addition, a laboratory-scale artificial wetland pilot model was built, and the aluminum sludge-polyurethane prepolymer adsorption material prepared in the present application was used to treat domestic wastewater containing carbon, nitrogen and phosphorus. After three months of periodic detection and observation, the removal performance of total phosphorus reached more than 90%, the COD removal rate reached more than 80%, and the ammonia nitrogen removal rate reached more than 85%, and the nitric nitrogen removal rate reached more than 80%. The new adsorption material obtained in the example of the present application has a good removal effect and application prospect.
[0084] In addition, in order to study the effect of the aluminum sludge-polyurethane prepolymer adsorption material prepared in this application on the removal of antibiotics from artificial wetland matrices, the adsorption kinetics was first used to verify the removal effect of the adsorption material on antibiotics (norfloxacin hydrochloride, oxytetracycline hydrochloride). The experimental results showed that the adsorption material had good adsorption effects on both norfloxacin hydrochloride and oxytetracycline hydrochloride. In the adsorption kinetics experiment, the removal rate of the adsorption material for norfloxacin hydrochloride was above 70%, and the removal rate of oxytetracycline hydrochloride reached 80%.
[0085] The removal performance of artificial wetlands for antibiotic wastewater in the laboratory was further explored. By selecting two typical antibiotics, sulfonamides and quinolones, which are the most widely used and most harmful in life, specifically sulfamethoxazole and norfloxacin, the aluminum sludge-polyurethane prepolymer adsorption filler prepared in the examples of the present application was cut into block fillers of about 2 cm and filled into artificial wetland columns. Periodic detection was carried out every 3 months, and it was found that the adsorption materials obtained in Examples 1-9 of the present application had a removal effect of about 75% for norfloxacin, and a removal performance of 70%-75% for sulfamethoxazole. More specifically, the adsorption material obtained in Example 5 had a removal effect of 77% for norfloxacin, a removal performance of 75% for sulfamethoxazole, and a removal effect of 92% for total phosphorus in domestic wastewater.
[0086] It can be seen that the adsorption material obtained in this application has a good removal potential for emerging pollutants such as antibiotics, and is of great significance for the actual engineering removal of antibiotic wastewater in the future.
[0087] Comparative Example 1
[0088] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material comprises the following steps:
[0089] S1. Mechanically dehydrating the collected aluminum sludge and then drying it to obtain an aluminum sludge raw material with a water content of 45%;
[0090] S2, then directly mixing the aluminum sludge raw material with a water content of 45% with the polyurethane prepolymer, mixing and stirring for 30 seconds at room temperature, and foaming to form blocks, wherein the addition mass ratio of the aluminum sludge raw material to the polyurethane prepolymer is 20:5;
[0091] S3. Let it stand for 2-5 minutes to solidify, and then air-dry to obtain the aluminum sludge-polyurethane prepolymer adsorption material.
[0092] It is seen that the adsorption material obtained in Comparative Example 1 has a slagging phenomenon, and its flexibility is lower than that in Example 5. The adsorption material obtained in Comparative Example 1 is also used in an artificial wetland laboratory model, and is tested periodically for three months. It is found that its removal effect on norfloxacin is 63%, and the removal performance on sulfamethoxazole is 60%. In addition, the removal effect on total phosphorus in domestic wastewater is 75%, and its removal effect is much weaker than that of the adsorption material prepared by mixing anhydrous aluminum sludge powder, polyurethane prepolymer and water in Example 5. This may be due to the fact that the foam formation process in the method affects the final structural stability and the establishment of the pore structure. In addition, the adsorption material prepared by the method has a slagging phenomenon when used for wastewater treatment, resulting in additional suspended solids in the water treatment, affecting the final treatment effect.
[0093] Finally, the preparation of the adsorption material in this application provides a good application approach for the resource utilization of sludge, realizes the resource recycling of water plant sludge, and achieves the purpose of treating waste with waste. In addition, traditional aluminum sludge cannot be used as an adsorbent for sewage or wastewater or as a filler for artificial wetlands. This application uses the simplest preparation method to produce aluminum sludge into an adsorption material with good removal performance, no slag, green and environmental protection, and easy transportation. It can be mass-produced and has great potential for practical engineering applications.
[0094] In addition, in order to further improve the removal effect of the adsorption material on antibiotics, modified PET-gasified slag composite filler is added to the raw material of the adsorption material.
[0095] Example 10
[0096] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 5, except that:
[0097] In step S2, a modified PET-gasified slag composite filler is added together with the anhydrous aluminum sludge powder, and the amount of the modified PET-gasified slag composite filler added is 15% of the amount of the anhydrous aluminum sludge powder added, and the modified PET-gasified slag composite filler is prepared by the following method:
[0098] Waste polyester and gasified slag were mixed in a mass ratio of 1:2 and calcined at 450°C for 2.5 hours, then soaked in dilute sulfuric acid with a mass concentration of 40wt% for 30 minutes, and the amount of dilute sulfuric acid solution added was 4.5 times the mass of the gasified slag. After filtration and separation, the mixture was washed with water, and then soaked in a mixed aqueous solution of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane for 1.5 hours and dried. The soaking temperature was 40°C to obtain a modified PET-gasified slag composite filler.
[0099] The added mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane is 1:2.5, and the added amount of 3-hydroxypropyltrimethoxysilane is 8wt% of the gasified slag addition amount, and the added amount of water is 3.5 mass times of 3-hydroxypropyltrimethoxysilane.
[0100] Embodiment 11
[0101] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 5, except that:
[0102] In step S2, a modified PET-gasified slag composite filler is added together with the anhydrous aluminum sludge powder, and the added amount of the modified PET-gasified slag composite filler is 10% of the added amount of the anhydrous aluminum sludge powder, and the modified PET-gasified slag composite filler is prepared by the following method:
[0103] Waste polyester and gasified slag were mixed in a mass ratio of 1:1.8 and calcined at 420°C for 3h, then soaked in dilute sulfuric acid with a mass concentration of 37wt% for 40min, the amount of dilute sulfuric acid solution added was 4 times the mass of the gasified slag, and then filtered and separated, washed with water, and then soaked in a mixed aqueous solution of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane for 1h and dried, the soaking temperature was 35°C, to obtain a modified PET-gasified slag composite filler.
[0104] The added mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane is 1:2, and the added amount of 3-hydroxypropyltrimethoxysilane is 5wt% of the gasified slag added amount, and the added amount of water is 3 mass times of 3-hydroxypropyltrimethoxysilane.
[0105] Example 12
[0106] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 5, except that:
[0107] In step S2, a modified PET-gasified slag composite filler is added together with the anhydrous aluminum sludge powder, and the added amount of the modified PET-gasified slag composite filler is 18% of the added amount of the anhydrous aluminum sludge powder, and the modified PET-gasified slag composite filler is prepared by the following method:
[0108] Waste polyester and gasified slag were mixed in a mass ratio of 1:2.2 and calcined at 500°C for 2h, then soaked in dilute sulfuric acid with a mass concentration of 45wt% for 20min, the amount of dilute sulfuric acid solution added was 5 times the mass of the gasified slag, and then filtered and separated, washed with water, and then soaked in a mixed aqueous solution of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane for 2h and dried, the soaking temperature was 50°C, to obtain a modified PET-gasified slag composite filler.
[0109] The added mass ratio of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane is 1:3, and the added amount of 3-hydroxypropyltrimethoxysilane is 10wt% of the gasified slag addition amount, and the added amount of water is 4 times the mass of 3-hydroxypropyltrimethoxysilane.
[0110] Embodiment 13
[0111] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that:
[0112] The waste polyester and gasified slag were calcined and then directly immersed in a mixed aqueous solution of N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane for 2 hours without acid washing.
[0113] Embodiment 14
[0114] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that an equal amount of N-2-aminoethyl-3-aminopropyltrimethoxysilane is replaced by 3-hydroxypropyltrimethoxysilane.
[0115] Embodiment 15
[0116] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that an equal amount of N-2-aminoethyl-3-aminopropyltrimethoxysilane is replaced by γ-aminopropyltriethoxysilane.
[0117] Example 16
[0118] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that an equal amount of gasified slag is replaced by waste polyester.
[0119] Embodiment 17
[0120] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that an equal amount of waste polyester is replaced by gasified slag.
[0121] Embodiment 18
[0122] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that PAMAM is also added to the soaking water solution to which N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane are added, and the amount of PAMAM added is 3wt% of the amount of gasified slag added.
[0123] Embodiment 19
[0124] A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material is carried out according to the method in Example 10, except that PAMAM is also added to the soaking aqueous solution to which N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane are added, and the amount of PAMAM added is 5wt% of the amount of gasified slag added.
[0125] The adsorption materials prepared in the above Examples 10-19 were used in an artificial wetland laboratory model and tested periodically every three months to test the removal rates of norfloxacin and sulfamethoxazole in antibiotic wastewater and total phosphorus in domestic wastewater. The results are shown in Table 4 below.
[0126] Table 4:
[0127]
[0128] Combined with the test results in Table 4 above, when modified PET-gasified slag composite filler is also added to the adsorbent material in Examples 10-12, the removal effect of antibiotics norfloxacin and sulfamethazine is significantly improved, and the removal effect of total phosphorus is further improved. Combined with the test results of Example 13, it can be seen that when the waste polyester and gasified slag are not pickled after calcination, the phosphorus removal effect is significantly reduced. After pickling, the gasified slag is converted into a soluble aluminum salt by converting its aluminum silicate into a soluble aluminum salt, further improving the removal effect of total phosphorus. Combined with the test results of Examples 14 and 15, when only 3-hydroxypropyltrimethoxysilane is added, the antibiotic effect is significantly reduced. When ordinary silane coupling agent KH-550 is selected in Example 15, the antibiotic effect is also reduced. Combined with Examples 16 and 17, when only gasified slag or waste polyester is added, the antibiotic removal effect is significantly reduced, especially when gasified slag is not added to the raw material, compared with Example 10, the removal effect is significantly reduced. Combined with the test results of Examples 18-19, the removal effect of antibiotics was further improved when PAMAM was added during the soaking treatment.
[0129] In addition, the adsorbent materials prepared in Examples 10-19 of the present application also did not have the phenomenon of slag falling. In addition, when the adsorbent material obtained in Example 10 of the present application is used for artificial wetlands to treat antibiotic wastewater, when hydrogen peroxide is added at the same time, when the amount of hydrogen peroxide added is 3-5wt% of the adsorbent material, it is found that the removal rate of norfloxacin in antibiotic wastewater reaches 94%, and the removal rate of sulfamethazine reaches 88%, which is significantly improved, and when treating domestic wastewater, the removal rate of COD reaches 86%, which is significantly improved compared to Example 5. This may be due to the metal oxides in the gasified slag being calcined to form nano-iron tetroxide, which catalyzes the formation of hydrogen peroxide to promote the production of hydroxyl radicals to decompose organic matter and improve its treatment effect.
[0130] The aluminum sludge-polyurethane prepolymer adsorption material prepared in the present application has an excellent pore structure and excellent adsorption performance, and has broad application prospects in the field of artificial wetland fillers or sewage treatment.
[0131] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing an aluminum sludge-polyurethane prepolymer adsorption material, characterized in that: The following steps are involved: S1, mechanically dehydrating and drying the collected aluminum sludge, crushing it, and grinding it to obtain anhydrous aluminum sludge powder; S2, mixing anhydrous aluminum sludge powder with water and polyurethane prepolymer, stirring and foaming; S3, standing and solidifying, and then air-drying to obtain an aluminum sludge-polyurethane prepolymer adsorption material; In step S2, a modified PET-gasified slag composite filler is further added, and the amount of the modified PET-gasified slag composite filler added is 10-18% of the amount of the anhydrous aluminum sludge powder added. The modified PET-gasified slag composite filler is prepared by mixing waste polyester and gasified slag, calcining at 420-500° C. for 2-3 hours, and then acid-leaching in a sulfuric acid solution, and then filtering and separating, and then washing with water to obtain a primary filler, and then treating with N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane; PAMAM is added while N-2-aminoethyl-3-aminopropyltrimethoxysilane and 3-hydroxypropyltrimethoxysilane are added, and the amount of PAMAM added is 3-5wt% of the amount of gasified slag added.
2. The method for preparing an aluminum sludge-polyurethane prepolymer adsorption material according to claim 1, characterized in that: In step S2, water and anhydrous aluminum sludge powder are firstly stirred to form a uniform slurry mixture, and then the polyurethane prepolymer is added and stirred for foaming at room temperature.
3. The method for preparing an aluminum sludge-polyurethane prepolymer adsorption material according to claim 1, characterized in that: In step S2, the added mass ratio of anhydrous aluminum sludge powder to water is (15-25):10, and the added mass ratio of water to polyurethane prepolymer is 10:(3-7).
4. The method for preparing an aluminum sludge-polyurethane prepolymer adsorption material according to claim 1, characterized in that: The specific operations in step S1 are: mechanically dehydrating the collected aluminum sludge, drying it in the sun, air-drying it, crushing it, grinding it and sieving it to obtain anhydrous aluminum sludge powder.
5. The method for preparing an aluminum sludge-polyurethane prepolymer adsorption material according to claim 1, characterized in that: The mass ratio of anhydrous aluminum sludge powder to water and polyurethane prepolymer added in step S2 is 20:10:
3.
6. The method for preparing an aluminum sludge-polyurethane prepolymer adsorption material according to claim 4, characterized in that: The anhydrous aluminum sludge powder in step S1 is the sewage aluminum sludge powder obtained after passing through an 80-150 mesh sieve.
7. An aluminum sludge-polyurethane prepolymer adsorption material prepared by the preparation method as described in any one of claims 1 to 6.
8. Use of the aluminum sludge-polyurethane prepolymer adsorption material as claimed in claim 7 in the field of artificial wetland filler or sewage treatment.
Citation Information
Patent Citations
Nitrogen and phosphorus removal composite adsorption material and preparation method thereof
CN109647337A
Method for preparing porous carbon material through polyester low-temperature carbonization
CN111410184A
A straw fiber adsorption material, its preparation methods and applications
GB202018479D0